The Potential of EU Connectivity through Missions and Smart Specialization - Šime, Zane (2023)
Mission-oriented innovation and smart specialisation are internationally familiar concepts. They hold the potential to add more profundity to the EU thinking and modelling of its connectivity approach towards Asia and the world in general. The existing policy, governance frameworks and implementation instruments of smart specialisation and innovation could provide connectivity with evidence-informed lessons learnt and research findings from various parts of the world. Both frameworks for innovation and research could steer the EU connectivity approach away from controversies tied to the weaponised interdependence and strategic autonomy, including the bundle of concepts that come along with this vulnerabilities-oriented intellectual current. Research-intensity and mutual learning are elements that the mission-oriented innovation and smart specialisation could bring to the overall spectrum of thematic dimensions and implementation measures of the EU approach towards sustainably and trustfully connecting to Asia and other parts of the world.